2002
DOI: 10.1128/jb.184.9.2455-2459.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved C-Terminal Region in Gp71 of the Small Isometric-Head Phage LL-H and ORF474 of the Prolate-Head Phage JCL1032 Is Implicated in Specificity of Adsorption of Phage to Its Host, Lactobacillus delbrueckii

Abstract: Thirty-five phage-resistant mutants of Lactobacillus delbrueckii subsp. lactis ATCC 15808 were selected. Thirty-three of these mutants were assigned to the Bes group, while the remaining two were grouped under the Ads designation. Bes group mutants adsorbed phage LL-H but did not allow efficient phage development. Preliminary evidence suggests that these strains exhibit a mutation that changes the DNA specificity of a restriction-modification system. The Ads group mutants did not adsorb the small isometric-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…We have previously suggested that there are at least three types of receptors for L. delbrueckii phages: two specific for LL-H and its host range mutant LL-H-a21 and one specific for the phage JCL1032 (23). In this study, we demonstrate that these L. delbrueckii phages are inactivated by purified LTAs from L. delbrueckii subsp.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…We have previously suggested that there are at least three types of receptors for L. delbrueckii phages: two specific for LL-H and its host range mutant LL-H-a21 and one specific for the phage JCL1032 (23). In this study, we demonstrate that these L. delbrueckii phages are inactivated by purified LTAs from L. delbrueckii subsp.…”
mentioning
confidence: 57%
“…As far as we know, LL-H-a21 differs from LL-H only by a single amino acid in the receptor binding protein Gp71, thus suggesting that the specificity of inactivation reactions resides in the Gp71-LTA interaction (23). Like LL-H-a21, JCL1032 reacted with the LTAs examined in this study, although more LTAs were needed for significant inactivation.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The LL-H gene product responsible for host recognition has been identified as Gp71 by utilizing the isolated LL-H-resistant mutant (Ads-5) of L. delbrueckii subsp. lactis ATCC 15808 and the LL-H host range mutants (35). The small isometric-headed phage LL-H, with a noncontractile tail, a baseplate, and a central tail fiber (5,21), exhibits only limited DNA similarity to another L. delbrueckii phage, JCL1032 (20,36).…”
mentioning
confidence: 99%